Exploratory study on the method of ecological design for landscape building - LIU Wen-ye; WANG Xiao-qi (浙江大学学报. 农业与生命科学版)
During the design of landscape building and environment, architects often face the problem of how to deal with the relationship between human and nature. In order to solve the problem, many architects used to study their instinct relations from such viewpoints as in space relationship, mental experience and human behavior. Guided by ecological principle, this paper focused on human beings as a part of the natural ecological system to make layout and design landscape building.